2021
DOI: 10.1021/acs.chemrev.1c00138
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-lactamases in the Age of Multidrug Resistance: From Structure and Mechanism to Evolution, Dissemination, and Inhibitor Design

Abstract: Antimicrobial resistance is one of the major problems in current practical medicine. The spread of genes coding for resistance determinants among bacteria challenges the use of approved antibiotics, narrowing the options for treatment. Resistance to carbapenems, last resort antibiotics, is a major concern. Metallo-β-lactamases (MBLs) hydrolyze carbapenems, penicillins, and cephalosporins, becoming central to this problem. These enzymes diverge with respect to serine-β-lactamases by exhibiting a different fold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
169
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 1,253 publications
2
169
0
1
Order By: Relevance
“…Metallo-hydrolase-like MBL-fold superfamily of proteins is a large and ancient group of proteins that are widely distributed over the kingdoms of bacteria, archaea, and eukarya. Sequence, structure, and biochemical studies revealed that the superfamily consists of members with diverse functions, consisting of class B β-lactamase, glyoxalase II (GLXII), N-acyl-L-homoserine lactonase (AHL), persulfide dioxygenase, flavodiiron protein, choline-binding protein, cleavage and polyadenylation specificity factors, arylsulfatase, 5 -exonuclease, ribonuclease, cyclic nucleotide phosphodiesterase, insecticide hydrolase, and proteins required for natural transformation competence [1][2][3][4]. Members of this superfamily contain conserved αβ/βα metallo-β-lactamase-fold (MBL-fold) domain, with two central β-sheets surrounded by solvent-exposed α-helices, and either have a mononuclear or binuclear metal binding site located at the interface of the β/β sandwich, characterized by the His-Xaa-His-Xaa-Asp-His motif [5].…”
Section: Introductionmentioning
confidence: 99%
“…Metallo-hydrolase-like MBL-fold superfamily of proteins is a large and ancient group of proteins that are widely distributed over the kingdoms of bacteria, archaea, and eukarya. Sequence, structure, and biochemical studies revealed that the superfamily consists of members with diverse functions, consisting of class B β-lactamase, glyoxalase II (GLXII), N-acyl-L-homoserine lactonase (AHL), persulfide dioxygenase, flavodiiron protein, choline-binding protein, cleavage and polyadenylation specificity factors, arylsulfatase, 5 -exonuclease, ribonuclease, cyclic nucleotide phosphodiesterase, insecticide hydrolase, and proteins required for natural transformation competence [1][2][3][4]. Members of this superfamily contain conserved αβ/βα metallo-β-lactamase-fold (MBL-fold) domain, with two central β-sheets surrounded by solvent-exposed α-helices, and either have a mononuclear or binuclear metal binding site located at the interface of the β/β sandwich, characterized by the His-Xaa-His-Xaa-Asp-His motif [5].…”
Section: Introductionmentioning
confidence: 99%
“…Infections sustained by metallo-β-lactamases (MBLs)-producing bacteria pose a global challenge due to the paucity of effective antibiotic options. Despite that MBLs account only for 10% of the total β-lactamases [ 1 ], these enzymes are capable of hydrolyzing all current available β-lactams, with the exception of monobactams, such as aztreonam (ATM) [ 2 ]. Differently from serine-β-lactamases, MBLs are Zn-dependent metalloproteinases which are non-susceptible to inactivation by currently available β-lactams inhibitors (BLIs), including vaborbactam (VAB), a cyclic boronate, and avibactam (AVI), a diazabicyclooctanone (DBO) derivative [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that non-specific porins on the cell membrane may also be involved in the transport of Zn 2+ from the outer membrane to the periplasmic space. P. aeruginosa regulates the expression of specific porins in response to Zn 2+ availability, such as OprD (Bahr et al, 2021). In addition, OprF is the most abundant non-lipoprotein outer membrane porin in P. aeruginosa, allowing ions and low molecular weight sugar molecules to pass through (Chevalier et al, 2017).…”
Section: Non-specific Membrane Transporters Mediate Zn 2+ Transportmentioning
confidence: 99%